Posttraumatic growth and psychosocial variables among victims of political violence - Gómez, Mauricio C. (2021)
Background: The Chilean military dictatorship (1973-1990) left thousands of victims among those directly affected and their families, who were able to develop various mental health sequelae. Objective: The present study sought to evaluate a predictive model of posttraumatic growth (PTG) that included political ideology, religious coping and rumination in victims of political violence during the dictatorship. Method: The study involved 200 adults recognised in the Programme for Reparation and Integral Health Care (PRAIS), which is responsible for providing support to direct victims of human rights violations and their family members during the dictatorship. Out of these, 104 were women (52%) and 96 were men (48%) ranging in age from 30 to 91 years. The Posttraumatic Growth Inventory, the Brief Religious Coping Scale, the Event-Related Rumination Scale and the Political Ideology Scale were used as instruments. Results: The main results indicated that positive religious coping and deliberate rumination predicted PTG. Deliberate rumination partially mediates between positive religious coping and PTG. Conclusion: It is concluded that positive religious coping and deliberate cognitive processing favour positive change in those directly affected by political violence and their family members. This reinforces the idea that victims of these violations manage to grow after these painful experiences. Authorship contributionMGR: conception and design of the study, data collection, data interpretation, discussion and writing of the manuscript.FEG: study conception and design, data analysis, data interpretation, discussion and final revision of the manuscript. final revision of the manuscript.